SecureCloud Guardian: Advancing Data Security via Advanced Dispersion and Encryption in Cloud Strorage (SCG) - Mrs. Viswanadapalli Anusha; Velagala Tata Naga Sai Subbi Reddy (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
Cloud storage, being one of the foundational pillars of modern computing, has been readily embraced and spurred fast growth in the cloud computing domain. Despite this massive and widespread acceptance, major security issues hang over the cloud storage scene and often result in huge security breaches and leaks of information. SecureCloud Guardian, or SCG, comes into the picture as an important instrument that guarantees privacy in information stored over the cloud. SCG follows a multi-pronged approach, including data dispersal techniques, storage distribution protocols, and encryption formats that guarantee efficient data storage. It also employs a hierarchical management approach that leverages user-level secret code as well as secret division algorithms for maintaining cryptographic material, preventing unauthorized access. The experimental studies carried out on SCG verify the effectiveness of this security-centered cloud storage technology in terms of avoiding data leakage. For instance, SCG uploads and downloads 5G files in a mere 646 seconds and 269 seconds, respectively—an attractive choice for consumers looking for secure cloud information storage.